Increasing Employee Job Performance, the Effects of Perceived Organizational Support and Transformational Leadership, Mediated By Work Engagement - Andri Pongoh; Andreas Gunawan; Justine Tanuwijaya (Jurnal Indonesia Sosial Teknologi, 2024)
Rapid developments in the financing industry sector in Indonesia have created a dynamic and challenging business competition. Sustainable business growth is one crucial achievement that is a point of competition between finance companies. Therefore, the optimal job performance of each employee is a significant factor. Previous studies has shown a connection between job performance with variables such as POS, transformational leadership, and work engagement in other industrial sectors. This study was aimed at analysing the influence of said variables among finance company employees in Central Jakarta and South Jakarta. The research was conducted in quantitative methods with primary data collection using questionnaires. The sample was taken using a purposive sampling technique, with a total of 250 respondents who are employees of finance companies in selected areas. Data analysis used the Structural Equation Model (SEM) with AMOS version 22 software and the Sobel Test to calculate the effects of each variable and its connection. This research results show that POS and transformational leadership have a positive influence on the job performance of finance company employees in Indonesia. It was also revealed that work engagement does have a mediating role in the relationship between the previous variables and job performance. In this context, the study indicates that factors from within and outside employees, such as POS and transformational leadership, play a role in improving their job performance by also increasing work engagement.